GAMBARAN HASIL UJI REAKTIF HEPATITIS B PADA DARAH DONOR DI UDD PMI KOTA MADIUN TAHUN 2017- 2020 - Shinta (Politeknik Kesehatan Bhakti Setya Indonesia, 2023)
Blood transfusion is an important form of health care. Giving according to indications can save lives and improve health status, to minimize the occurrence of infectious diseases through blood transfusions, especially HIV/AIDS, Hepatitis C, Hepatitis B, Syphilis, Malaria, and Dengue Hemorrhagic Fever (DHF). needed. Hepatitis B is a clinical or pathological syndrome characterized by varying degrees of inflammation and necrosis of the liver, caused by the Hepatitis B Virus. Infection can be acute or chronic, continuous without healing for at least six months. Mechanism of occurrence Acute hepatitis, chronic or hepatocellular carcinoma begins with liver cell damage. The purpose of this study was to determine the prevalence of Hepatitis B reactive test results on donor blood at UDD PMI Madiun in 2017-2020. The type and design of this study used descriptive with a quantitative approach to the population in this study, namely donors whose blood was screened for Hepatitis B Transmissible Infections (IMLTD) at UDD PMI Madiun from 2017 to 2020 as many as 51,481 donors. The sample used in this study was data from Hepatitis B reactive screening results on blood donors from 2017 to 2020 as many as 433 donors. The data analysis method in this study used a purposive sampling technique. Based on research on the Description of Hepatitis B Reactive Test Results on Blood Donors at UDD PMI Madiun City in 2017-2020, the number of reactive Hepatitis B based on the type of voluntary donor was 433 donors (100%) replacement donors 0 donors (0%), based on gender there were males -342 male donors (79.0%), 91 female donors (21.0%), based on age <18-24 years 78 donors (18.0%), 25-44 years 237 donors (54.7%) , 45-64 years 118 donors (27.3%), based on blood type there are group A 90 donors (20.8%), group B 137 donors (31.6%), group O 152 donors (35.1%) and group AB 54 donors (12.5%). All results of reactive HbsAg at UDD PMI Madiun City are voluntary donors.